Challenges Faced by Apprentices in Completing Dual TVET Course: A Case of Butwal Technical Institute (Journal of Technical and Vocational Education and Training, 2024)
This article highlights a case on the status of apprentices studying at Butwal Technical Institute (BTI), a pioneer not-for-profit apprenticeship education provider in Nepal. It is seen that the graduates of BTI are earning respectable income and living reputed life; however, the study incompletion rate is found significantly on rise at BTI. To identify the challenges faced by the apprentices to complete their study, a research was carried out, assuming inadequate family support or guidance, poor family economy, unfriendly working environment in the industry, institutional technical inefficiency, and unavailability of amenities in the institute as the five major challenges. As a descriptive method, a questionnaire was used for collecting data from 204 apprentices out of 314 in the study. The family support was a moderate challenge for the apprentice to complete their dual TVET apprenticeship training at BTI. The apprentices of BTI had normal financial support from their families. Another challenge was the environment of industry for the apprentices to complete the dual TVET apprenticeship training at BTI, while institutional technical efficiency was considered a moderate challenge to this regard.